2006
DOI: 10.1002/bdrb.20083
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine death, fetal malformation, and delayed pregnancy in Ljungan virus‐infected mice

Abstract: LV is found in different species of native animals in both Europe and the United States and human epidemiological evidence connects LV and human reproduction, while the observations here indicate that LV is responsible for reproductive problems in a laboratory mouse model. The current findings suggest that the hypothesis that LV also causes disease in pregnant women and their offspring deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…This pathogen, subsequently named the Ljungan virus (LV), has been identified in wild voles in Denmark and the United States, as well as in lemmings and inbred laboratory rats (Johansson et al, 2003;Niklasson et al, 2003aNiklasson et al, , 2006aNiklasson et al, , 2007aSamsioe et al, 2006). In addition, LV has been shown to induce type 2-like diabetes, uterine resorptions, malformations, and neonatal death in CD-1 laboratory house mice (Niklasson et al, 2006b;Samsioe et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This pathogen, subsequently named the Ljungan virus (LV), has been identified in wild voles in Denmark and the United States, as well as in lemmings and inbred laboratory rats (Johansson et al, 2003;Niklasson et al, 2003aNiklasson et al, , 2006aNiklasson et al, , 2007aSamsioe et al, 2006). In addition, LV has been shown to induce type 2-like diabetes, uterine resorptions, malformations, and neonatal death in CD-1 laboratory house mice (Niklasson et al, 2006b;Samsioe et al, 2006).…”
mentioning
confidence: 99%
“…In addition, LV has been shown to induce type 2-like diabetes, uterine resorptions, malformations, and neonatal death in CD-1 laboratory house mice (Niklasson et al, 2006b;Samsioe et al, 2006). It has also been noted that the manifestation of various symptoms in LV-infected animals increases with stress (Freimanis et al, 2003;Niklasson et al, 2003aNiklasson et al, , b, 2006bSamsioe et al, 2006). Intriguingly, in Sweden it has been shown that the incidence of type 1 diabetes, GuillainBarré syndrome, and myocarditis in the human population is correlated with rodent population cycles (Niklasson et al, 1998), and children newly diagnosed with type 1 diabetes have significantly increased levels of LV antibodies compared to controls (Niklasson et al, 2003a).…”
mentioning
confidence: 99%
“…Dams pregnant for the first time were injected intraperitoneally with either LV in normal saline or normal saline alone on the second gestational day; both groups of dams were also stressed by weighing them frequently throughout gestation and performing one glucose tolerance test with intraperitoneal glucose injection in a concentration of 100 mg/ml with blood collected from the tail vein. Six of seven infected dams but only one of seven control dams gave birth to dead pups; however, the number of pups per pregnancy did not differ between the two groups (Samsioe et al, 2006). It appears that only one (1.4%) of approximately 70 pups from infected dams had macroscopically identifiable malformations consisting of exencephaly and eight rib pairs.…”
Section: Fetal Death and Congenital Malformationsmentioning
confidence: 84%
“…Suckling, but not adult, mice, separately injected intraperitoneally with LV, developed clinical signs of encephalitis, but histologic studies of the brain were not undertaken, and rates of apparent encephalitis were not reported (Niklasson et al, 2006). In a separate study by these investigators, microscopic examination of the brains of six suckling mice (from one infected and stressed dam) with signs of encephalitis sacrificed 1 week after birth revealed vascular endothelial ''basophilia'' and hypercellularity but apparently not inflammation (Samsioe et al, 2006). In another study, each of the 47 infected offspring of four pregnant NMRI mouse dams (Charles River Laboratories, Kisslegg, Germany) infected with LV intraperitoneally 24-48 hours after birth revealed clinical signs of ''encephalitis'' compared to none of the 52 control suckling mice (p 5 0.0018) (Niklasson et al, 2009b).…”
Section: Encephalitismentioning
confidence: 99%
See 1 more Smart Citation